Role of Broad-Complex (Br) and Krüppel homolog 1 (Kr-h1) in the Ovary Development of Nilaparvata lugens - Jiang, Jianru; Xu, Yili; Lin, Xinda (Frontiers in Physiology, 2017)
Ovarian development plays an important role in the life history of insects and is crucial for control of the insect population. The metamorphosis of an insect is precisely regulated by the interaction of the juvenile hormone and ecdysone. To understand the role of NlBr and NlKr-h1 in ovary development, we used RNA interference (RNAi) to down-regulate the expression of Broad-Complex (Br) and Krüppel homologue 1 (Kr-h1), two important down-stream transcription factors of juvenile hormone and ecdysone signalling. We further investigated their effects on metamorphosis and ovary development. The results showed that both NlBr and NlKr-h1 are induced by ecdysone. The down-regulation of NlBr and NlKr-h1 alone or together by RNAi is more effective than the topical application of ecdysone on the number of ovarioles, suggesting the necessity of NlBr and NlKr-h1 in determining the number of ovarioles. The ovarian grade was significantly increased/decreased by the topical application of ecdysone and down-regulation of NlBr and NlKr-h1. The pre-oviposition period was also increased. When NlBr and NlKr-h1 were down-regulated together, the ovary grade was not significantly different compared to the control (dsGFP), indicating that the development of the ovary is under the control of both NlBr and NlKr-h1. The interaction between the NlBr and NlKr-h1 on the number of ovarioles and the development of the ovary indicates cross-talk between both juvenile hormone and ecdysone signalling at the transcription level in the brown planthopper. Both genes are nuclear transcription factors and may regulate signalling via down-stream genes. These results would help to both enhance the current understanding of the regulatory mechanism of the interaction between juvenile hormone and ecdysone signalling pathways during ovarian development and to design chemicals to control pests.